An Analysis of Room Reservation Practice Learning Obstacle for Students in The Second Diploma of Accommodation at The Community Academy of MAPINDO - Agustina Riski, Gusti Ayu (Jurnal Manajemen Pelayanan Hotel, 2023)
Room Reservation practice is one of the courses that aims to prepare students so that they have the competenceto handle room requests, process bookings, and archive the history of room bookings. Learning in the practiceof booking rooms uses the role play method, where students act as reservation agents and others as guestswith the material being Room Reservation procedures via telephone operator. However, in the learningprocess, there are several obstacles in learning that hinder the achievement of the objectives of the learningoutcomes. The purpose of this research is to analyze the types of difficulties experienced by students along withthe factors that cause them as well as the efforts made by students to overcome these obstacles so that learningabout the practice of booking rooms can run in accordance with the stated objectives. The research methodused is a qualitative method, collecting data through observation, distributing questionnaires, interviews anddocumentation. Respondents in this study were 29 students, selected purposively (purposive sampling),namely students who had experiences in practical learning process for booking rooms. Analysis techniques usequalitative data. The research results show that students have difficulty recording guest payment methods,allocating rooms, providing room rates, and filling in reservation charts. The causal factors are divided intointernal factor (such us: lack pf confidence, and language barriers) and external factor (lak of facilities and timeallocating). The efforts made by students are to study again and practice a lot of role plays, as well as lookingfor references from other sources.Keywords: Barriers, Learning, Front Office Practice, Front Office Practice